ELECTRIC FIELD AND CURRENT DENSITY CHARACTERISTIC OF CONTAMINATED SOLID INSULATOR - Sunthrasakaran, Nishanthi; Mohd Jamail, Dr. Nor Akmal; Shee Kandar, Mohd Haris Asyraf (International Journal of Integrated Engineering, 2018)
The performance of an insulator may degrade over a time period. One of the main factor is due to presence of contamination on the insulator which leads to flashover, corona and damages the insulator. This study focuses on overhead XLPE cables used in distribution system with voltage rated 33kV. The contaminants are varied in order to study the behaviour of electric field and current density of the XLPE insulator. Contaminant used in this study is sodium chloride, lead and rain water. Quickfield software was used to draw and simulate the contaminated cable. The electrical conductivity of cable and contamination was used to represent every layer of the drawing. From the result produce, analysis on the electric field and current density of a contaminated and non-contaminated insulator was made. Analysis shows that the contaminated insulator has higher electrical field and current density compared to non-contaminated insulator. When the electrical conductivity is high, the electric field is the lowest and the current density is the highest in the insulator. Whereas, the XLPE insulator with sodium chloride contamination has the highest current density followed by rain water and lead because the conductivity of sodium chloride is the highest. The electric field strength of lead is the highest followed by rain water and sodium chloride.